Tinjauan Literatur mengenai Tingkat Infestasi Ektoparasit pada Udang Vaname (Litopenaeus vannamei) di Sistem Tambak Budidaya - Medina Masri; Robiah Al Adawiyah (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2025)
The shrimp farming industry in Indonesia is predominantly dominated by Vannamei shrimp (Litopenaeus vannamei), also known as white shrimp. This shrimp species is favored due to its fast growth rate and high economic value. However, the intensive farming practices often lead to various diseases, particularly those caused by parasitic infections. Ectoparasitic infections can create wounds on the shrimp’s body, making it easier for other pathogens like fungi, bacteria, and viruses to invade. This study aims to identify the types and levels of ectoparasite infestations on Vannamei shrimp to understand their impact on shrimp health and farm productivity. The research method used is a literature review, gathering data from various sources such as scientific journals, books, research reports, and technical notes related to shrimp farming. The findings of the study show that the presence of ectoparasites can serve as an important indicator to assess the health of the farming environment. High levels of parasitic infestations indicate suboptimal environmental conditions, such as poor water quality or improper management practices. Therefore, early identification of ectoparasites is crucial to prevent the spread of diseases and ensure the sustainability of Vannamei shrimp farming in Indonesia.